Islamic Education in the Digital Era: Building the Mental Health of Generation Z for A Quality Future - Indriana, Nina; Ridwan, Mohammad; Hisniati, Sally Badriya; Abdullah, Asep; Hasanah, Aan; Arifin, Bambang Samsul (Budapest International Research and Critics University, 2024)
This article aims to explain the crucial role of Islamic education in maintaining the mental health of Generation Z in the digital era. By analyzing current trends, this research highlights the safety and wellbeing challenges facing Generation Z, including the negative impact of technology on mental health. The research method involved a literature review and analysis of current data regarding social media use and its impact. The research results show that the integration of Islamic values in digital education has a significant role in guiding Generation Z to manage technology healthily. The gap between technological advances and mental health can be overcome through learning Islamic values which include digital literacy and social media ethics. The novelty of this article lies in its holistic approach to the well-being of Generation Z, emphasizing healthy digital literacy and ethics in the context of Islamic education.